2014
DOI: 10.1523/jneurosci.3228-13.2014
|View full text |Cite
|
Sign up to set email alerts
|

Autonomous Encoding of Irrelevant Goals and Outcomes by Prefrontal Cortex Neurons

Abstract: Two rhesus monkeys performed a distance discrimination task in which they reported whether a red square or a blue circle had appeared farther from a fixed reference point. Because a new pair of distances was chosen randomly on each trial, and because the monkeys had no opportunity to correct errors, no information from the previous trial was relevant to a current one. Nevertheless, many prefrontal cortex neurons encoded the outcome of the previous trial on current trials. A smaller, intermingled population of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

6
47
2

Year Published

2014
2014
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 49 publications
(55 citation statements)
references
References 53 publications
6
47
2
Order By: Relevance
“…However, we found that only a small number of recorded units (6.3%, 12 out of all 192 neurons; 7.8%, 8 out of 103 AGl neurons; 4.5%, 4 out of 89 AGm neurons) were modulated by the previous choice factor. In the Genovesio et al (2014) study, the percentage of primate PFC neurons showing a significant effect of the previous choice decreased to a chance level soon after trial start. However, they observed much higher percentage of neurons with effect of the previous outcome factor.…”
Section: Discussionmentioning
confidence: 84%
See 2 more Smart Citations
“…However, we found that only a small number of recorded units (6.3%, 12 out of all 192 neurons; 7.8%, 8 out of 103 AGl neurons; 4.5%, 4 out of 89 AGm neurons) were modulated by the previous choice factor. In the Genovesio et al (2014) study, the percentage of primate PFC neurons showing a significant effect of the previous choice decreased to a chance level soon after trial start. However, they observed much higher percentage of neurons with effect of the previous outcome factor.…”
Section: Discussionmentioning
confidence: 84%
“…Significant evidence from primate and rodent studies indicated a widespread neural modulation in response to previous outcome during learning. Trial outcome as a transient event was shown clearly encoded in single unit activity in PFC (Narayanan and Laubach 2008;Histed et al 2009;Genovesio et al 2014), anterior cingulate cortex (Seo and Lee 2007;Quilodran et al 2008), striatum (Histed et al 2009), andhippocampus (Wirth et al 2009). The signal was sustained in the intertrial interval and carried over to the next trial, which may have contributed to linking past outcomes with future actions (Donahue et al 2013).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Reward responses are found also in premotor, prefrontal, cingulate, insular, and perirhinal cortex (8,246,369,569). Some prefrontal neurons code the reward of the preceding trial (30,179).…”
Section: Events Eliciting Reward Responsesmentioning
confidence: 99%
“…More recently, we studied [76] previous goal representation in the PFd and periarcuate cortex (PA) in a distance discrimination task (figure 4a), in which the task of the monkey did not require previous trial monitoring and the monkeys were not trained in other tasks that required it. In this task, the monkeys were instructed to determine which of two stimuli, presented sequentially at different distances from the screen centre, was the farthest away.…”
Section: Does Previous Goal Encoding Depend On Task Relevance?mentioning
confidence: 99%